From fear to awe in Luzzatto's Mesillat Yesharim - Garb, Yehonatan (European journal of jewish studies, 2020)
Perhaps the key term in musar writing is yir’ah. In early modern musar texts, usually incorporating kabbalistic discourse, this term is rendered as 'fear'. A striking exception is R. Moshe Ḥayyim Luzzatto’s Mesillat Yesharim, arguably one of the canonical texts of Jewish modernity. A close reading of the chapters devoted to yir’ah reveals that Luzzatto frames this term as ‘awe,’ moving away from the discourse on punishment and hell typical of early modern musar. An examination of the psychology behind this move shows that Luzzatto associates fear with the lower instinct of self-preservation, calling for its sublimation into self-abnegation in awe of divine presence. Mesillat Yesharim then became foundational for similar moves in later Jewish modernity. Without wishing to venture into claims as to inter-religious influence and response, it is instructive to compare Luzzatto’s approach to that of his Christian contemporaries, the ‘fire and brimstone’ preachers of the Great Awakening.